Kekuatan Tarik Dan Porositas Silinder Al-Mg-Si Hasil Die Casting Dengan Variasi Tekanan - Irawan, Yudy Surya; Oerbandono, Tjuk; Agus Aristiyono, Dian Fitria; Pratikto, Pratikto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
Tensile strength and porosity of die-casted Aluminum Alloys Al-Mg-Si with various applied pressure were investigated. Al-Mg-Si was melt in the electric induction crucible with temperature of 850 degree Celsius. Melt aluminum was poured in the metallic mould that pre-heated in 150 degree Celsius. Melt aluminum was pressed by the plunger with pressure of 0.1, 10, 30, and 50 MPa and held for 5 minutes. After aluminum was solidified, specimens for tensile strength and porosity test were machined. Tensile strength, porosity test and microstructure observation were conducted. Results of tensile strength and porosity test show that the higher plunger pressure, porosity becomes lower and tensile strength of specimens to be higher. Maximum tensile strength occurs in the specimens that pressed in 50 MPa. It occurs due to minimum porosity and small grains of microstructure in the specimens.Keywords : Aluminum, Die casting, Pressure, Tensile Strength, Porosity, Microstructure